189k views
1 vote
F(x) = Yx - 9. Find the inverse of f(x).

User Hemaulo
by
4.4k points

1 Answer

5 votes

SOLUTION

To find the inverse, first, we will make x the subject of the formula:


\begin{gathered} y=\sqrt[3]{x-9} \\ \text{Cube both sides} \end{gathered}
\begin{gathered} y^3=(\sqrt[3]{x-9})^3 \\ y^3=x-9 \\ y^3+9=x \end{gathered}

Now we will replace x with f-inverse and replace y with x in the above expression:


\begin{gathered} f^(-1)(x)=x^3+9 \\ \text{The correct answer is D.} \end{gathered}

User Nipun Talukdar
by
5.1k points